Manejo de cenicilla (Oidium sp.), en el cultivo de mora (Rubus Glaucus) en el cantón Tisaleo (Tungurahua). - Telenchana Tiban, Miguel Ángel (2024)
The objective of the research was to evaluate the chemical control of powdery mildew (Oidium sp.) through the use of Acord, ZT and Sul flox in the cultivation of Blackberry (Rubus glaucus) in the Tisaleo canton. A 4*7 factorial arrangement was used implemented with a Randomized Complete Block Design with three repetitions applying an experimental and hypothetical investigation. The incidence and severity of powdery mildew was evaluated, in addition to the impact that this disease has on blackberry production and the relationship of precipitation in the area on the impact of the disease, as well as a severity scale for powdery mildew was developed. in arrears. In each lot of the study, a main branch was chosen on each plant to evaluate the incidence and in the same branch a leaflet from the middle zone was chosen where the severity was evaluated, to observe the impact of the disease on production, a a fruit count at the beginning and end. The result was that Acord at a dose of 1.25 cc was the best fungicide that controlled powdery mildew, obtaining a 15.67% incidence in the town of San José and a 3% severity in the town of Santa Lucia, like this product. It does not affect blackberry production, as in the town of Chilco an increase of 0.09 kg/plant was obtained. In addition, it should be mentioned that the variables incidence and severity vs. precipitation corroborate that the lower the precipitation, the greater the presence of powdery mildew.